Plan de alta en cuidados de enfermería en el recién nacido - Fernández Romero, Celia Alexandra; Ayala Huacon, Cristhian Josue; Aguilar Ramírez, Mayra Patricia (My University, 2022)
Introduction: Around the world, 270,000 babies are born daily, most of them spend a short time in hospital rooms, so their care continues at home, for this reason mothers should receive education on the management of the newborn and thus reduce the risks of complications. and early death Objective: To develop a discharge plan on home care of the newborn addressed to mothers. Development: The newborn has an immature body different from that of children and adults, this increases their vulnerability, so they need specific care in daily activities such as hygiene, feeding, pediatric check-ups, and then tests such as metabolic screening must be performed. Performing these procedures correctly reduces the risk of illness and neonatal death, and also gives tools to mothers, reducing stress rates, contributing to the comprehensive recovery of their health. Methodology: A survey was applied to 75 postpartum women from the Teofilo Davila General Hospital at the time of discharge. Conclusion: The mothers presented a deficit in knowledge about the techniques of caring for the newborn at home, which evidenced that there are communication gaps between nursing staff and puerperal women, for which it was concluded that the development of a discharge plan is necessary whose content explains in detail care such as daily bathing, navel cleaning, feeding, importance of metabolic screening, vaccination, pediatric controls, this must be accompanied by education by the nursing staff to ensure that the information is received. Keywords: discharge plan; Nursing; Newborn.
Introducción: Alrededor del mundo nacen 270,000 bebés diariamente, la mayoría permanecen poco tiempo en las salas hospitalarias por lo que su cuidado continúa en casa, por esto las madres deben recibir educación sobre el manejo del recién nacido y de esa manera reducir los riesgos de complicaciones y muerte precoz Objetivo: Elaborar un plan de alta sobre los cuidados en casa del recién nacido direccionado a las madres. Desarrollo: El recién nacido tiene un organismo inmaduro diferente al de los niños y adultos esto hace que aumenta su vulnerabilidad, por lo que necesita cuidados específicos en actividades cotidianas como higiene, alimentación, controles pediátricos, además luego debe realizarse exámenes como el tamizaje metabólico, realizar correctamente estos procedimientos reduce los riesgos de enfermedades y muerte neonatal, además otorga herramientas a las madres reduciendo los índices de estrés contribuyendo la recuperación integral de su salud. Metodología: Se aplicó una encuesta a 75 mujeres puérperas del hospital general Teofilo Davila al momento de recibir el alta Conclusión: Las madres presentaron déficit en el conocimiento sobre las técnicas de cuidado en casa del recién nacido, lo que evidenció que existen brechas de comunicación entre el personal de enfermería y las puérperas, por lo que se concluyó que la elaboración de un plan de alta es necesario cuyo contenido explique detalladamente cuidados como baño diario, limpieza de ombligo, alimentación, importancia del tamizaje metabólico, vacunación, controles pediátrico, este debes ser acompañado de educación por parte del personal de enfermería para asegurar que la información sea recibida.
Keywords: PLAN DE ALTA; ENFERMERIA; RECIEN NACIDO